2022
DOI: 10.3390/pr10101952
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of IoT Communication Protocols Using Anomaly Detection with Security Assessments of Smart Devices

Abstract: The authors implemented an attack scenario that involved simulating attacks to compromise node and sensor data. This research proposes a framework with algorithms that generates automated malicious commands which conform to device protocol standards and bypass compromise detection. The authors performed attack-detection testing with three different home setup simulations and referred to Accuracy of Detection, Ease of Precision, and Attack Recall, with the F1-Score as the parameter. The results obtained for ano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Many researchers have presented an extensive review on IoT communication protocols and architecture. [1][2][3] F I G U R E 1 Prisma diagram of the proposed survey.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have presented an extensive review on IoT communication protocols and architecture. [1][2][3] F I G U R E 1 Prisma diagram of the proposed survey.…”
Section: Introductionmentioning
confidence: 99%
“…These applications collect the data from the IoT devices and help in analyzing the data. Many researchers have presented an extensive review on IoT communication protocols and architecture 1‐3 …”
Section: Introductionmentioning
confidence: 99%
“…These studies concluded that the of-grid hybrid renewable systems for rural areas are more effective. Other studies about the off-grid hybrid power systems in Saudi Arabia were presented [20][21][22][23][24][25]. Amran et al, reviewed the current and future status of renewable energy potential in Saudi Arabia such as wind, solar, geothermal, hydro, and biomass [26].…”
Section: Introductionmentioning
confidence: 99%